1991
DOI: 10.1111/j.1651-2227.1991.tb11825.x
|View full text |Cite
|
Sign up to set email alerts
|

Breast Feeding Modifies Production of SlgA Cow's Milk‐Antibodies in Infants

Abstract: One hundred and fifty-eight healthy mature newborns were divided into 3 groups according to their risk of allergy: Group A, no risk (n = 62), group B, low risk (n = 30) and Group C, high risk (n = 66). Saliva was collected at birth and after 3 and 6 months. SIgA anti-casein and anti-beta-lactoglobulin were determined by a direct ELISA technique. The highest concentrations of secretory antibodies were measured after birth. After 3 months, breast fed infants had lower salivary SIgA anti-casein concentrations tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
3

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 10 publications
0
4
0
3
Order By: Relevance
“…Human milk reduces the risk for infections, with a greater effect in non-atopic than in atopic infants (1,2). Human colostrudmilk enhances gut maturation and provides passive protection for bacteria and antigens (allergens) by specific secretory IgA and other protecting factors (3,4), even after a short nursing period of only 3 weeks (5). However, most of the beneficial effects of breast milk are only related to fresh milk (6), although the incidence of cow's milk protein allergy (CMPA) in infants fed own mother's milk or pasteurized pooled human milk was also reported equal (1.7%) (7).…”
Section: Y Vandenplas Az-kinderen Free University Of Brussels Lamentioning
confidence: 99%
“…Human milk reduces the risk for infections, with a greater effect in non-atopic than in atopic infants (1,2). Human colostrudmilk enhances gut maturation and provides passive protection for bacteria and antigens (allergens) by specific secretory IgA and other protecting factors (3,4), even after a short nursing period of only 3 weeks (5). However, most of the beneficial effects of breast milk are only related to fresh milk (6), although the incidence of cow's milk protein allergy (CMPA) in infants fed own mother's milk or pasteurized pooled human milk was also reported equal (1.7%) (7).…”
Section: Y Vandenplas Az-kinderen Free University Of Brussels Lamentioning
confidence: 99%
“…Not only do these Abs provide passive protection against infections, but they might also actively shape childhood immunity and tolerance induction by providing the fetus and the infant with the mother's immunological experience (12). In this regard, the diaplacental transfer of IgG Abs and the presence of high amounts of secretory IgA Abs in breast milk might play an important role (13). However, whether the T cell compartment might also be actively involved in regulating pre-and postnatal immunity has not been extensively studied to date.…”
mentioning
confidence: 99%
“…Breast‐feeding appears to modulate secretory (S)‐IgA production in infants, even if the mode of this effect is controversial (11–13). We have earlier reported that the levels of IL‐10 and TGF‐β, that both regulate IgA production, correlate with the levels of SIgA in breast milk (4).…”
mentioning
confidence: 99%